Application of the hollow fibre infection model (HFIM) in antimicrobial development: a systematic review and recommendations of reporting. (28th June 2021) - Sadouki, Zahra; McHugh, Timothy D.; Aarnoutse, Rob; Ortiz Canseco, Julio; Darlow, Christopher; Hope, William; van Ingen, Jakko; Longshaw, Christopher; Manissero, Davide; Mead, Andrew; Pelligand, Ludovic; Phee, Lynette; et al.
Abstract: Objectives: This systematic review focuses on the use of the in vitro hollow fibre infection model (HFIM) for microbial culture. We summarize the direction of the field to date and propose best-practice principles for reporting of the applications. Methods: Searches in six databases (MEDLINE ®, EMBASE ®, PubMed ®, BIOSIS ®, SCOPUS ® and Cochrane ® ) up to January 2020 identified 129 studies meeting our inclusion criteria. Two reviewers independently assessed and extracted data from each publication. The quality of reporting of microbiological and technical parameters was analysed. Results: Forty-seven out of 129 (36.4%) studies did not report the minimum pharmacokinetic parameters required in order to replicate the pharmacokinetic profile of HFIM experiments. Fifty-three out of 129 (41.1%) publications did not report the medium used in the HFIM. The overwhelming majority of publications did not perform any technical repeats [107/129 (82.9%)] or biological repeats [97/129 (75.2%)]. Conclusions: This review demonstrates that most publications provide insufficient data to allow for results to be evaluated, thus impairing the reproducibility of HFIM experiments. Therefore, there is a clear need for the development of laboratory standardization and improved reporting of HFIM experiments.